2017
DOI: 10.1021/jacs.6b11226
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Interactions between Graphene and Biological Molecules

Abstract: Applications of graphene have extended into areas of nanobio-technology such as nanobio-medicine, nanobio-sensing, as well as nanoelectronics with biomolecules. These applications involve interactions between proteins, peptides, DNA, RNA etc. and graphene, therefore understanding such molecular interactions is essential. For example, many applications based on using graphene and peptides require peptides to interact with (e.g., noncovalently bind to) graphene at one end, while simultaneously exposing the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
128
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(131 citation statements)
references
References 80 publications
2
128
1
Order By: Relevance
“…The modulation of charge at the graphene‐liquid interface is possible by the attachment of a broad range of organic or inorganic chemical functionalities to the graphene surface . This allows the realization of sensors for targets like DNA, peptides, and proteins ,. As in carbon electrodes, the interfacial charge of graphene is modulated by the presence of chemical moieties covalently or non‐covalently attached to the surface.…”
Section: Introductionmentioning
confidence: 99%
“…The modulation of charge at the graphene‐liquid interface is possible by the attachment of a broad range of organic or inorganic chemical functionalities to the graphene surface . This allows the realization of sensors for targets like DNA, peptides, and proteins ,. As in carbon electrodes, the interfacial charge of graphene is modulated by the presence of chemical moieties covalently or non‐covalently attached to the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Affinity biosensor manufacture requires bio-functionalization of the graphene surface with an analyte-specific receptor [ 5 ]. Adsorption of proteins to a graphene surface for use in biosensors requires the protein to remain in a particular conformation, ensuring one part of the protein is in contact with the graphene surface (required for adsorption stability and electron doping) and another specific part is exposed to the solvent/solution phase (required for receptor-analyte binding) [ 6 , 7 ]. Protein adsorption to a surface is a complicated process involving van der Waals, hydrophobic, and electrostatic interactions, and hydrogen bonding [ 8 ], with process conditions, such as ionic strength, pH, and temperature also contributing factors [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Protein adsorption to a surface is a complicated process involving van der Waals, hydrophobic, and electrostatic interactions, and hydrogen bonding [ 8 ], with process conditions, such as ionic strength, pH, and temperature also contributing factors [ 9 ]. Non-covalent interactions between proteins and graphene depend on the binding affinity of various residues in the protein as well as the distribution of the residues [ 6 ] and it has not been explicitly shown that a protein remains functional after adsorption onto graphene surfaces [ 10 ]. Therefore, different unique proteins could interact differently with the graphene surface, potentially affecting the proteins’ structure and binding capability.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that being used as a catalyst support is the main application of carbon nanotubes (CNTs) in the field of fuel cells mainly due to its advantages such as the simple preparation process, high specific surface area, higher electric conductivity, good thermal and chemical stability . Recently, the large‐scale application of CNTs has become a reality because of the sharp decline in the CNTs preparation cost, as compared to some novel kinds of carbon like carbon nanofiber and graphene . Thus, expanding the applications of CNTs has turned into a hot topic especially for the CNTs‐related electrochemical researchers …”
Section: Introductionmentioning
confidence: 99%